Comment on "Use of deterministic models in sports and exercise biomechanics research" by Chow and Knudson (2011) - Glazier, P. S.; Robins, M. T. (Sports Biomechanics, 2012)
In a recent issue of Sports Biomechanics,Chowand Knudson (2011) provided a comprehensive historical review and an update of the application and utility of deterministic models in both performance- and injury-related sports and exercise biomechanics research. They argued that these models, which were originally introduced and popularised by the late James Hay and his co-workers (e.g. Hay & Reid, 1988), could provide a much-needed theoretical basis for applied sports biomechanics research thereby helping sports biomechanists to explain, rather than merely describe, mechanical aspects of athletic performance and also limit the number of trivial studies being reported in the sports biomechanics literature. Although Chow and Knudson (2011) made some convincing and robust arguments in favour of the use of deterministic models in sports biomechanics research, there are a number of caveats that we believe need to be considered before adopting this approach.